2004
DOI: 10.1130/b25357.1
|View full text |Cite
|
Sign up to set email alerts
|

GPS measurements from the Ladakh Himalaya, India: Preliminary tests of plate-like or continuous deformation in Tibet

Abstract: Observations of relative motion in a geodetic network in Ladakh, India, and across southern Tibet indicate slow shear on the Karakorum fault, rapid east-west extension across the whole of southern Tibet, and constant arc-normal convergence between India and southern Tibet along the Himalayan arc. Measurements of ten campaign-style and six permanent sites with global positioning system (GPS) precise geodesy provide these bounds on the style and rates of the large-scale deformation in the Tibet-Himalaya region. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
100
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 151 publications
(108 citation statements)
references
References 36 publications
(71 reference statements)
7
100
1
Order By: Relevance
“…The surprising proximity of the 1803 and 1991 earthquakes is suggestive that one may be a recurrence of the other. In 188 years, the present day convergence rate would result in a slip deficit of greater than 3 m, more than sufficient to drive an M 6.8 earthquake (Jade et al, 2004). The 1819 Allah Bund Earthquake…”
Section: Case Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The surprising proximity of the 1803 and 1991 earthquakes is suggestive that one may be a recurrence of the other. In 188 years, the present day convergence rate would result in a slip deficit of greater than 3 m, more than sufficient to drive an M 6.8 earthquake (Jade et al, 2004). The 1819 Allah Bund Earthquake…”
Section: Case Studiesmentioning
confidence: 99%
“…Thus, according to our intensity analysis, the 1833 and 1866 earthquakes both appear to have ruptured similar locations in the Nepal Himalaya with similar magnitudes. In this case, unlike the 1803/1991 earthquake pair, the slip in the second event would not have developed over the course of 33 years with a geodetic convergence rate of 18 mm=yr (Jade et al, 2004). *Columns a, b, c, and d refer to the variables in equation (1).…”
Section: The 1833 and 1866 Nepal Earthquakesmentioning
confidence: 99%
“…The depth is consistent with the earthquake rupturing the base of the crust, and is consistent with the compressional state of stress beneath the Karakoram today, but similar to the deep earthquakes beneath Nepal-southern Tibet, it is likely that elevated temperatures in the middle crust preclude earthquakes beneath the Karakoram. Jade et al (2004) suggested that active right-lateral slip along the Karakoram Fault could be no more than 3.4 mm a À1 based on GPS measurements.…”
Section: Earthquakes Along the Karakoram Faultmentioning
confidence: 99%
“…The data set of He et al [2013] contains 16 campaign-mode sites located in a localized dense network across central segment of Altyn Tagh Fault from the Tarim Basin to northern Tibet and measured twice in the period of 2009-2011. In addition, we show published velocities for surrounding regions (Figure 1): from the Nepal Himalaya [e.g., Banerjee et al, 2008;Bettinelli et al, 2006;Bilham et al, 1997;Feldl and Bilham, 2006], northwest Himalaya [Banerjee and Bürgmann, 2002], Pamir-Hindu Kush [Ischuk et al, 2013;Mohadjer et al, 2010], Kashmir and Ladakh Himalaya [e.g., Jade et al, 2004;Schiffman et al, 2013], eastern Himalaya, Naga Hills, and Shillong Plateau [Devachandra et al, 2014;Vernant et al, 2014].…”
Section: Gps Velocity Field and Its Implicationsmentioning
confidence: 99%
“…East-west extension in southern Tibet is part of an active strain rate field that includes overthrusting of the Himalaya onto India in a direction perpendicular to the local strike of the range; the rigidity of the Indian plate and the curvature of the range require such extension of southern Tibet [e.g., Armijo et al, 1986;Copley and McKenzie, 2007;Jade et al, 2004;Chen, 1982, 1983;Molnar and Lyon-Caen, 1989;Styron et al, 2011]. Moreover, because gradients in horizontal normal stresses should, in general, lie parallel to gradients in gravitational potential energy [e.g., England and Jackson, 1989;England and McKenzie, 1982], the radial overthrusting at the Himalaya is a likely consequence of any rheological structure or vertical distribution of flow, whether that flow occurs without shear on horizontal planes as in a thin viscous sheet [e.g., England and Molnar, 1997], as channel flow [e.g., Clark and Royden, 2000;Royden, 1996], or as a gravity current [Copley, 2012;Copley and McKenzie, 2007].…”
Section: Introductionmentioning
confidence: 99%